SISTEM KENDAL1 SOFT-STOPPING PADA MOTOR INDUKSI TIGA FASE BERBASIS MIKROKONTROLER (Soft-Stopping Control System in Three Phases Induction Motor Based on Microcontroller) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
Accurate timing is strongly needed in a moving control system in modern industries, especially in industries using three phases induction motor as .a part of their production equipment. This study was - intended to evaluate the performance of soft-stopping control system of three phases induction motor based on microcontroller by adding thyristor hold off angle for the purpose of timing. This control system detects time of null intersection of source tension and detect losing of current from ggl versus motor when the control do soft opening activity. Soft stopping process of the control begins from soft start to steady state condition and to soft stopping when loaded current reach minimum value. Within the process of soft-stopping, the addition of thyristor hold off angle gradually, wailing for the calculation of the working circle from its microcontroller, for the purpose of programmed timing. This study was carried out in three-phase induction motor of 220/380 Volt, power of 0.5 Hp, and load of 72.4 Watt. Result of this study indicated that minimum current when stopping was on thyristor hold off angle wide position (y) of 44.9D, mistake of timing during an hour was 0.34% (12.2 seconds late) in condition of unloaded motor and 0.35% (12.5 seconds late) in loaded motor condition.